2020
DOI: 10.3390/cancers12102979
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of let-7e MicroRNA and Its Target Genes in Localized High-Risk Intestinal GIST: A Spanish Group for Research on Sarcoma (GEIS) Study

Abstract: MicroRNAs (miRNAs) are small non-coding RNAs that negatively regulate gene expression at the post-transcriptional level, and they have been described as being associated with tumor prognosis. Here, miRNA profiling was planned to explore new molecular prognostic biomarkers in localized intestinal high-risk GIST. Paraffin tumor blocks of 14 and 86 patients were used in the discovery and expansion sets, respectively. GeneChip miRNA v3.0 was employed to identify the miRNAs differentially expressed between relapsed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 50 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…Remarkably, IGF1R has been found negatively regulated in let-7e overexpressing HCT-116 and LoVo cell lines [ 34 , 35 ]. Moreover, let-7e expression negatively correlates with ACVR1B in gastrointestinal stromal tumors (GIST) [ 36 ]. Altogether these results confirmed our observation in mice, and further sustain a possible involvement of let-7e in the differentiation process of intestinal epithelial cells rather than in the proliferation ones.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, IGF1R has been found negatively regulated in let-7e overexpressing HCT-116 and LoVo cell lines [ 34 , 35 ]. Moreover, let-7e expression negatively correlates with ACVR1B in gastrointestinal stromal tumors (GIST) [ 36 ]. Altogether these results confirmed our observation in mice, and further sustain a possible involvement of let-7e in the differentiation process of intestinal epithelial cells rather than in the proliferation ones.…”
Section: Discussionmentioning
confidence: 99%
“…40 Studies have revealed that IL10 mediates the activity of MAPK pathway, AMPK pathway, and JAK/STAT pathway, [41][42][43] and COL3A1 was identified as the regulatory factor of MAPK pathway. 44 MMP2, as a kind of downstream gene, was found to be regulated by MAPK pathway, Wnt pathway, and JAK/ STAT pathway, which were involved in the pathophysiological process of ischemia-reperfusion injury. [45][46][47] Thus, all the top 8 mRNAs may play important roles in the prediction and treatment of this disease, an area that warrants further research.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, genetic alterations, epigenetic mechanisms play a key role in disease biology by controlling gene expression at the post-transcriptional level [ 3 , 17 ]. In this context, research interest in miRNAs has quickly increased and several studies have investigated the role of miRNAs in GIST development, classification, and prognosis [ 18 , 19 , 20 ]. However, most of the studies focused on KIT mutants or KIT/PDGFRA wild-type (WT) GISTs, leaving the molecular biology of PDGFRA -mutant GISTs largely unexplored.…”
Section: Introductionmentioning
confidence: 99%